When Human Behavior Enters the Equation. Issue 3 (2nd October 2018) - Larsen, Philip
ABSTRACT: In political science, there is a profound tension between those who argue that the prediction of human behavior is possible and those who disagree. On the one hand, experimental methods may be able to detect behavioral patterns. On the other hand, events, the evolution of institutions, and individual behavior itself may in many cases be too historically contingent to be reliably predicted. Methodological pluralism, and a greater degree of openness to mere historical understanding, would therefore seem to be called for.